TINJAUAN PENYEBAB DUPLIKASI PENOMORAN REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH CIKALONG WETAN - Gunawan, Edih; -, Sumarna (Jurnal TEDC; Vol 19 No 1 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i1.1164, 2025)
The duplication that occurs is only one patient with more than one medical record number but there is also duplication in the form of one medical record number. Based on observations in the medical record unit of the Cikalong Wetan Regional General Hospital in the filling and registration section, duplicate medical record numbering was found, this occurred because the patient did not carry a medical card, the hospital system was disrupted, filling and discontinuity of the contents of the patient’s medical record. The purpose of this study was to determine the cause of duplication of medical record numbering at the Cikalong Wetan Regional General Hospital. The research method used is a descriptive method with a qualitative approach.  Data collection techniques are interview, observation and documentation studies. Non-probability sampling is used. The results of the research using the triangulation method were, the patient did not carry a medical card, the hospital system was disrupted, officer discipline, education background, the expedition book was still manual, the filling section was one of the factor causing duplication of medical numbering. The author suggests conducting discussion, education ang training and providing Computerized Patient Record (CPR) facilities in the filling section.